KOMUNIKASI KELUARGA DALAM UPAYA BERINTERNET SEHAT DI RT IV RW XI KELURAHAN DELIMA KECAMATAN TAMPAN PEKANBARU - Suryani, Wan Murni; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Healty is the common good internet users are wise to behave in the virtual world as it could be done in compliance with the norms, values, and customs regulations. Meanwhile family first and foremost as a vehicle for the generation of qualified growth required to prepare along with the continued development of information technology and the industry that can carry a positive or negative impact for children. The authors study aimed to determine communication patterns are applied parents of children in the surf healthy adolescents in RT IV RW XI handsome village districts Pekanbaru pomegranate and family communication in an effort to know the healthy surfing at RT IV RW XI village pomegranate Pekanbaru handsome districts. Identifikasi in the study were how is the communication patterns are applied parents of children in the surf sound at RT IV RW XI village districts pomegranate tampan Pekanbaru? How is the communication of healthy families in an attempt to surf at RT IV RW XI pomegranate village districts Pekanbaru handsome?This study used a qualititative method with descriptive approach. Subjects were 3 (three) families in RT IV RW XI village Pomegranate Handsome Pekanbaru District of the specified categories based on purposive sampling. The collection of data obtained through interviews and documentation.The results showed that in RT IV RW XI Village Pomegranate District of Handsome Pekanbaru, Communication patterns in internet usage of three family each unlike single family using communication pattern authoritarian, one family communication patterns permissive (frees), and one family other authoritative communication patterns (democratic). Third family also trying to noting public opinion on its environment. Because of environmental monitoring also needed to provide browsing activity limitation on environmental public citizen, to use technology to things that good and healthy for life.Kata Kunci : Komunikasi Keluarga, Internet Sehat, Kelurahan Delima